On the Extent of Tyrosine Phosphorylation in Chloroplasts. Issue 2 (4th August 2015) - Lu, Qintao; Helm, Stefan; Rödiger, Anja; Baginsky, Sacha
Abstract : Reanalysis of published mass spectrometry data on Tyr-phosphorylated chloroplast proteins indicates that the majority of peptide spectrum matches reporting Tyr phosphorylation are ambiguous.